Mechanical Response Characteristics of Cu–Ta Alloys Under Detonation and High-Speed Impact - Yiming Li; Wenbin Li; Ping Song; Peng Chen; Wenjin Yao; Xiaoming Wang (Shock and Vibration)
To improve the strength of the shaped-charge jet and thereby enhance the penetration power of warheads, the Cu–30Ta alloy with a Cu/Ta mass ratio of 7:3 was prepared based on powder metallurgy technology. The mechanical response characteristics of the Cu–30Ta alloy under dynamic impact were investigated. The strain, strain rate, temperature, and jet strength distributions of Cu–10Ta and Cu–30Ta shaped-charge jets were comprehensively compared, and the plastic deformation mechanisms of the two alloys were analyzed from a microscopic perspective. The results show that the strain-hardening behavior of the Cu–10Ta alloy was more pronounced than that of the Cu–30Ta alloy. The Cu–Ta alloy exhibits good thermal stability. When the ambient temperature rises to 50% of the melting point of the alloy, the stress-softening amount of both alloys was lower than 15% of the initial strength. The average strength of Cu–30Ta alloy jet is 345.91 MPa, which is 42.2% higher than that of Cu–10Ta alloy jet. The Cu phase was the main source of the Cu–Ta plastic deformation ability, and the Ta particles mainly underwent morphological elongation, with limited contribution to the total deformation of the jet. In addition, with increasing Ta content, collision and extrusion of the Ta particles during the jet-formation process intensified, improving the plastic deformation resistance of the material, thereby leading to an improvement in the overall strength of the Cu–Ta alloy.